Tokenization 0f MSME Assets in Defi: Opportunities, Risks, and Hybrid Governance Architecture - Kiruthika Dhanapal; Peter Waher (Generate Digital Publishing, 2025)
Objective: This study aims to comprehensively analyze the transformative potential of asset tokenization for Micro, Small, and Medium Enterprises (MSMEs) within the Decentralized Finance (DeFi) ecosystem, with a focus on opportunities, risks, and the hybrid governance architecture required.Research Design & Methods: This study uses a qualitative approach, combining a systematic literature review and case studies with thematic content analysis of secondary data from credible sources to identify patterns and key themes.Findings: Findings show that tokenization of MSME assets offers significant opportunities, such as broader and faster access to funding through fractionalization of ownership, increased asset liquidity, operational efficiency, and enhanced transparency and security. However, this implementation is accompanied by various risks, including smart contract vulnerabilities, cyber attacks, blockchain scalability challenges, regulatory uncertainty, market volatility, and operational risks related to reliance on off-chain third parties. A hybrid governance architecture that integrates on-chain and off-chain elements is essential to mitigate these risks. Implications & Recommendations: This study indicates that tokenization can be an essential bridge for MSMEs to enter the global digital economy, but it requires improved digital literacy and technological readiness. For investors, it offers new diversification opportunities with inherent risks. Policy recommendations include adaptive regulation, simplified compliance, digital education, infrastructure strengthening, utilization of regulatory sandboxes, and cross-sector collaboration and standardization.Contribution & Value Added: This study presents a comprehensive framework for tokenizing MSME assets, offering practical guidance for various stakeholders to promote financial inclusion and equitable economic growth.